Analisis Peluang terhadap Penilaian Kinerja Pegawai Menggunakan Metode Regresi Linier Berganda dengan SPSS - Billy Nugraha; Wahyudin Wahyudin; Fahriza Nurul Azizah (Performa: Media Ilmiah Teknik Industri, 2021)
Research on human resource development have been carried out. With the aim of can be used as parameters to create the development of quality human resources. This research aims to know the influence of opportunities on the assessment of the performance of employees. Opportunities under study is divided into three indicators, namely the environment, the rules and colleagues. Sampling technique in this study using a sampling of saturated. The technique of data analysis was conducted gradually, starting from the editing, coding, scoring and tabulation. In addition, using a likert scale developed by Ransis Likert. While for the development of research using statistical methods, it is necessary to qualify the classical assumption test before the test is conducted multiple linear regression. It aims to determine how much significance of significance testing. The results from the hypothesis t, there is on the value tcount for the partial (sequential) starting from X1 = 2,639, X2 = 3,379 and X3 = 2,210. In addition, the results of the hypothesis F, contained in the value of Fcount simultaneously (together) was 12,597. While the value of R Square (R2) of 0,282, if then the result of 28.2%. It can be concluded from the three independent variables affect the dependent variable by 28,2%.